Analytic Philosophy, Theism, and Contemporary Philosophy of Religion - Penner, Myron Arthur (Toronto journal of theology, 2013)
Klaas J. Kraay's 2013 Newman Lecture, "Method and Madness in Contemporary Analytic Philosophy of Religion" is a valuable survey of and interaction with four recent works by philosophers of religion, each of which advances arguments concerning how philosophy of religion ought to be pursued, given the relatively high percentage of theists in the field. My response to Kraay's stimulating lecture will focus on the phenomenon of "insider" vs "outsider" perspectives in the study of religion, as well as some comments on and supplements to Kraay's survey.